(3ebGdI aj GdaUOs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3bGd jfRd Yf GdYVdI fMh GddMe , hdG jaUO UjakG aEfg jQe , hdG jecf JTHjg YfO Pdc GdEcMGd jfYbO , aEf cGf GdYUH jefJg Ch jSQJg aUO HTYQI GdeHVY NdGa LgI GdYVH s
(3BNQgG (B:s
(3EeG Cf jJQcg Efg dG HCS Hg , hEeG Gf jMd eG bO LeO ai ae GdVQHI ef GdOe HTYQI GdeHVY aEf Pdc CUdM s
(3Vef eLehY , JQJjHgG (B: (3ef U (B169 - (3U(B171s
(3GfXQgG eY GdeQTO Qbe (B" 730"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B249 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThGQi edi (B(1538) s
Keywords: (3GdWHs